Lifetime Risk of Heart Failure Among Participants in the Framingham Study - Vasan, Ramachandran S; Enserro, Danielle M; Beiser, Alexa S; Xanthakis, Vanessa (Journal of the American College of Cardiology, 2022)
The residual lifetime risk (RLR) of developing heart failure (HF) may have changed over time because of the increasing population burden of hypertension, obesity, and diabetes; greater survival after myocardial infarction; and a greater lifespan. The authors assessed changes in the RLR for HF in two 25-year epochs (1965-1989 and 1990-2014). We compared the RLR of HF at age 50 years (adjusting for competing risk of death) in the 2 epochs in Framingham Study participants overall and in the following strata: sex, body mass index, blood pressure, and diabetes. Mean life expectancy increased from 75.9 to 82.1 years in women and 72.5 to 78.1 years in men. We observed 624 HF events over 111,351 person-observations in epoch 1, and 875 HF events over 128,903 person-observations in epoch 2. The mean age at onset of HF increased across the epochs by 6.6 years (women) to 7.2 years (men). The RLR of HF at age 50 years increased across epochs from 18.86% to 22.55% (absolute increase 3.69; 95% CI: 0.90-6.49; P = 0.01) in women, and from 19.19% to 25.25% (absolute increase 6.06; 95% CI: 3.08-9.04; P < 0.001) in men. The increase in RLR of HF in the second epoch was consistent across strata with excess body mass index or higher blood pressure (relative increase of 28%-47%) and in participants without prior myocardial infarction (relative increase of 23%). The RLR of HF has increased in our community-based sample of White individuals over the last 5 decades, possibly caused by an increase in life expectancy.